Obesity may be erythropoietin dose-saving in hemodialysis patients - Ghada M. El-Kannishy; Abir F. Megahed; Mona M. Tawfik; Ghada El-Said; Rabab T. Zakaria; Nahed A. Mohamed; Eman M. Taha; Alzhraa A. Ammar; Abeer M. Abd Eltawab; Nagy A. Sayed-Ahmed (The Korean Society of Nephrology, 2018)
Background : In dialysis patients, the obesity-survival paradox still requires an explanation. Anemia and high doses of erythropoiesis-stimulating agents (ESAs) are associated with worse outcomes in the hemodialysis (HD) population. In the present study, we explored the relation between obesity and anemia control in a sample of maintenance HD patients in Egypt. Methods : This multicenter observational study included 733 patients on maintenance HD from 9 hemodialysis centers in Egypt. Clinical and laboratory data as well as average doses of ESAs and parenteral iron were recorded. The erythropoietin resistance index (ERI) was calculated. Results : Obesity, defined as a body mass index (BMI) ≥ 30 kg/m², was present in 22.6% of the studied population. The target hemoglobin level (10.0-11.5 g/dL) was achieved in 27.3% of non-obese and 25.3% of obese patients, with no significant difference. The median serum ferritin and the values of transferrin saturation index did not differ significantly between these two groups. The weekly ESA dose was significantly lower in obese than in non-obese patients (P = 0.0001). A trend toward higher ESA doses and ERI values was observed in patients with lower BMIs (P ＜ 0.0001). Multiple linear regression revealed that the BMI and urea reduction ratio were the strongest predictors of the ERI. Conclusion : Our study adds more evidence to obesity-associated advantages in HD patients. BMI may determine ESA response, with better responses observed in patients with higher BMIs.